(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Machinov V. N. Lingvodidactical potential of intercultural communication as a category of methods of teaching foreign languages. The article examines theoretical basics of intercultural communication as a category of methods of foreign language teaching and their linguistic and didactic potential, substantiated the new intercultural paradigm, which is based on the concept of forming the language personality, which opens up opportunities to search for new optimal ways of improving foreign language education students.